2015
DOI: 10.1159/000380907
|View full text |Cite
|
Sign up to set email alerts
|

Low-Dose versus Standard-Dose Intravenous Immunoglobulin to Prevent Fetal Intracranial Hemorrhage in Fetal and Neonatal Alloimmune Thrombocytopenia: A Randomized Trial

Abstract: Objective: Pregnancies at risk of fetal and neonatal alloimmune thrombocytopenia (FNAIT) are commonly treated using weekly intravenous immunoglobulin (IVIG) at 1 g/kg maternal weight. IVIG is an expensive multidonor human blood product with dose-related side effects. Our aim was to evaluate the effectiveness of IVIG at a lower dose, i.e. 0.5 g/kg. Methods: This was a randomized controlled multicenter trial conducted in Sweden, the Netherlands and Australia. Pregnant women with human platelet antigen alloantibo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 21 publications
3
21
0
Order By: Relevance
“…IVIG only treatment had a 98.7% success rate for preventing ICH (4 ICHs occurred in 315 pregnancies). 16,17,[19][20][21][22][23][24][26][27][28][29][30][31][32]34,35 This is consistent with the rate of 97.3% found in the Cochrane analysis reported by Rayment et al, 16 which included 37 pregnancies treated with IVIG only. However, none of the studies were powered to detect a significant difference in bleeding outcomes.…”
Section: Main Findingssupporting
confidence: 79%
See 3 more Smart Citations
“…IVIG only treatment had a 98.7% success rate for preventing ICH (4 ICHs occurred in 315 pregnancies). 16,17,[19][20][21][22][23][24][26][27][28][29][30][31][32]34,35 This is consistent with the rate of 97.3% found in the Cochrane analysis reported by Rayment et al, 16 which included 37 pregnancies treated with IVIG only. However, none of the studies were powered to detect a significant difference in bleeding outcomes.…”
Section: Main Findingssupporting
confidence: 79%
“…Whether the commonly used dose of 1 g/kg per week is the best treatment for all FNAIT pregnancies, or whether this could be reduced or increased in certain subgroups remains unclear. Data from the previously described randomized controlled trial 30 and retrospective data provided by Van Der Lugt et al 31 showed that the lower dose of 0.5 g/kg per week appeared not to be inferior to the 1 g/kg per week IVIG in standard risk (ie, a previous sibling that did not have an ICH) populations. Given the dose-related side effects and costs, a dose of 0.5 g/kg per week could be regarded as suitable for these women.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This study was prematurely ended in 2008 due to lack of inclusion [8] . The registry was kept open for fetal treatment centres worldwide to enter data on pregnancies complicated by FNAIT.…”
Section: Data Collectionmentioning
confidence: 99%